Real-Time Pore Blockage Quantification in Hydropower Drainage Pump Inlets via Canny Edge Detection and HSV Segmentation (Informatica, 2025)
As a core component of the diversion tunnel in hydropower stations, the drainage pump is prone to blockage in its inlet filter due to severe water calcification inside the tunnel. In this study, the present study proposes a computer-vision-based detection method to assess the blockage degree of the inlet filter's pores. Specifically, the outline of the small pores in the inlet screen of the drainage pump unit was captured using the Canny edge detection algorithm. Then the pore and non-pore areas of the filter were distinguished with the HSV color model. Finally, the degree of blockage was determined by calculating the proportion of pore areas within the filter screen. When applied to a real hydropower station using 12 images sampled at 15-day intervals, this developed computer vision technology achieved 13.6% average error against manual annotations and demonstrated real-time processing (